New study of the 1755 earthquake source based on multi-channel seismic survey data and tsunami modeling - M. A. Baptista; J. M. Miranda; F. Chierici; N. Zitellini (Copernicus Publications, 2003)
In the last years, large effort has been done to carry out multi-channel seismic reflection surveys (MCS) in SW Iberia to locate the active tectonic structures that could be related to the generation of the 1755 Lisbon earthquake and the tsunami. The outcome of these researches led to the identification of a large, compressive tectonic structure, named Marques de Pombal thrust that, alone can account for only half the seismic energy released by the 1755 event. However, these investigations have shown the presence of additional tectonic structures active along the continental margin of SW Iberia that are here evaluated to model the tsunami waves observed along the coasts of Iberia, Morocco and Central Atlantic. In this paper we present a new reappraisal of the 1755 source, proposing a possible composite source, including the Marques de Pombal thrust fault and the Guadalquivir Bank. The test of the source is achieved through numerical modelling of the tsunami all over the North Atlantic area. The results presented now incorporate data from the geophysical cruises and the historical observation along the European coasts and also from the Western Indies. The results of this study will, hopefully, improve the seismic risk assessment and evaluation in the Portuguese territory, Spain, Morocco and Central/North Atlantic.